The Influence of Organizational Culture and Organizational Commitment on Empoyee Performance at the Office of Population Control and Family Planning of Palopo City - Runi, Ishak; Sari, Idha; R, Mutia Ramadani; Risnayanti, Risnayanti; Nurfadila, Nurfadila (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2025)
This study aims to analyze the influence of organizational culture and organizational commitment on employee performance at the Office of Population Control and Family Planning (KB) in Palopo City. The research was conducted using a quantitative approach with data collected through observation, interviews, and questionnaires distributed to all 33 employees. Data were analyzed using multiple linear regression techniques, including validity and reliability tests, classical assumption tests, and hypothesis testing through t-tests and F-tests. The results show that organizational commitment has a positive and significant effect on employee performance, while organizational culture does not have a significant effect when tested partially. However, when tested simultaneously, both organizational culture and commitment jointly have a significant influence on employee performance. The coefficient of determination (R) value of 0.722 indicates that 72.2% of the variation in employee performance can be explained by the two independent variables. These findings highlight the importance of strengthening organizational commitment and cultivating a supportive organizational culture as strategic efforts to improve employee performance and the quality of public services.